Knowledge of sexually transmitted HPV infection, genitoanal warts, cancer and their prevention among young females after vaccine introduction in Germany. (6th December 2012) - Kuznetsov, A.V.; Müller, R.A.; Ruzicka, T.; Herzinger, T.; Kuznetsov, L.
Abstract Background Sexually transmitted human papillomavirus (HPV) high‐risk types cause carcinoma and low‐risk types lead to warts of genitoanal area. Since the HPV vaccine has been introduced, awareness of HPV infection, prevention and health‐related behaviour have not been studied in a large sample of young women in Germany. Objectives Assessment of awareness and health‐related behaviour regarding HPV infection and prevention among young German females. Methods In 2010, a postal cross‐sectional survey was conducted with a random representative sample size (n = 2000) of females aged 19–35 attending Germany's largest (comprehensive) university, which was designed to obtain data about socio‐demographics, the awareness of sexually transmitted HPV, genitoanal neoplasms and their prevention, HPV vaccine, immunisation and cervical cancer screening. Results Of the 547 (27.3%) participants, 69.1% had heard of HPV, 62.5% were aware of the vaccine, 14.4% were vaccinated and 6.9% reported a history of sexually transmitted infection, including HPV (2.7%). The HPV‐related knowledge among those who had heard of it was high (75.1–99.7%), except of that HPV affects men (52.9%) and HPV's causative role in genital (54.2%) and anal (35.6%) warts, and smoking (11.3%) as an HPV risk factor. The lower HPV knowledge score (<median = 12, ranged 1–17) was predicted by studying social sciences/humanities (OR = 3.68, 95% CI 1.99–6.79) and non‐participation in cervical cancer screening (OR = 2.04, 95% CI 1.02–4.07). Conclusion This survey reveals an insufficient HPV awareness and low vaccination prevalence among young German women, underscoring the urgent need for HPV‐related education aimed at reducing the burden of HPV‐induced genitoanal neoplasms.